2017
DOI: 10.1016/j.devcel.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vein Malformations Result from Loss of Twist1 Expression and BMP Signaling from Skull Progenitor Cells and Dura

Abstract: Dural cerebral veins (CV) are required for cerebrospinal fluid reabsorption and brain homeostasis, but mechanisms that regulate their growth and remodeling are unknown. We report molecular and cellular processes that regulate dural CV development in mammals, and describe venous malformations in humans with craniosynostosis and TWIST1 mutations that are recapitulated in mouse models. Surprisingly, Twist1 is dispensable in endothelial cells but required for specification of osteoprogenitor cells that differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 42 publications
2
37
1
Order By: Relevance
“…A recent study investigated development of the cerebral veins specifically. They found that TWIST1‐controlled production of BMP2 and BMP4 from the endosteal dura mater and the calvarial bone were important for the growth and remodeling of the cerebral veins (Tischfield et al, ).…”
Section: Influence Of the Meninges On Brain Developmentmentioning
confidence: 99%
“…A recent study investigated development of the cerebral veins specifically. They found that TWIST1‐controlled production of BMP2 and BMP4 from the endosteal dura mater and the calvarial bone were important for the growth and remodeling of the cerebral veins (Tischfield et al, ).…”
Section: Influence Of the Meninges On Brain Developmentmentioning
confidence: 99%
“…The development of these tissues is affected in neurocristopathies, which can be traced to mutations in genetic determinants of NCC specification and differentiation (Etchevers et al, 2019). As an example, mutations in transcription factor TWIST1 in human are associated with craniosynostosis (Ghouzzi et al, 2000) and cerebral vasculature defects (Tischfield et al, 2017). Phenotypic analyses of Twist1 conditional knockout mouse revealed that TWIST1 is required in the NCCs for the formation of the facial skeleton, the anterior skull vault, and the patterning of the cranial nerves (Soo et al, 2002;Ota et al, 2004;Bildsoe et al, 2009;Bildsoe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the inactivation of BMP2 and BMP4 using Wnt1-Cre in preosteoblasts and periosteal dura can result in defective skull and cerebral veins. BMP2/BMP4, which can be secreted from CNC or mesoderm-derived preosteoblasts and dura, can function in a paracrine manner to regulate the morphogenesis of the cerebral veins (Tischfield et al, 2017), revealing the unrecognized importance of BMP signaling in the maintenance of tissue-tissue interactions for craniofacial organ growth ( Table 1). Bone morphogenetic protein receptors are heterodimers complex composed of type I receptors and type II receptors.…”
Section: Functions Of Bmp Signaling In the Development Of Cranial Bonesmentioning
confidence: 99%